Birds of the pantanal floodplains, brazil: Historical data, diversity, and conservation - Nunes, Alessandro Pacheco; Posso, Sérgio Roberto; da Frota, Angélica Vilas Boas; Vitorino, Breno Dias; Laps, Rudi Ricardo; Donatelli, Reginaldo José [UNESP]; Straube, Fernando Costa; Pivatto, Maria Antonietta Castro; de Oliveira, Dalci Maurício Miranda; Carlos, Braulio; de Melo, Alyson Vieira; Tomas, Walfrido Moraes; et al. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
The Pantanal floodplains of Brazil are a region of rich biodiversity. To date, the true richness of the Pantanal avifauna has not been explored satisfactorily caused by a lack of studies in the region and, especially, by the divergence of opinion among the works published by various authors on the many species found in the region. This is due to the lack of criteria in examining records, both with regard to the reliability of the identifications and in the precise geographical allocation. Therefore, in the study, we collage findings from various studies and records created by us in the last few decades from 199 distinct locations to produce a list of birds in the Pantanal floodplains. We grouped the results into three lists: primary, secondary, and tertiary. We found that the avifauna of the Pantanal floodplain is composed of a total of 617 species, of which 571 (92%) have supporting records of occurrence (primary list) and 46 still lack documentation (secondary list). The number of species listed here for the Pantanal floodplain represents 32% of all avifauna known to the Brazilian territory. This reflects the importance of the biome, as part of the national territory, for the maintenance of a meaningful avifaunistic richness. Migratory birds (n = 183), notably northern ones (n = 43), are among the main players involved in ecological processes of nutrient cycling and dispersion of important pathogens between the two continents. With regard to conservation, 25 species are included in some category of threat in the lists of threatened species with global extinction. We hope that our list will help future researchers a more definitive approach when researching the avian fauna in this bountiful region.
Keywords: Biogeographic distribution; Birds; Migration; Threatened species; Wetlands and marshes